Cognitive Biases in Understanding the Influence of Shale Gas Exploitation: From Environmental and Economic Perspectives - Hu, Hui; Lin, Jingtong; Liu, Lu; Wu, Yufeng (Frontiers in Energy Research, 2021)
People have higher expectations for shale gas exploitation. However, the promotion of large-scale shale gas exploitation does not seem to be as good as it seems, since the extraction technology - hydraulic fracturing - harms the environment, which causes cognitive biases. This paper reviews studies that estimate the environmental and economic influence of the fracturing process in the U.S. and China to help people better understand the shale gas exploitation. It summarizes the methodological issues and results of main projections. There are shared problems in evaluating the influence of shale gas development due to limited identification methods, data sources and advancing exploitation technologies. Little research values the environmental influence of shale gas development in social benefit or economic benefit. Though varies significantly across various plays and parameter compared with conventional gases, previous researches indicate that water use for shale gas development will not affect the local water supply vastly, and the ultimate influence relies on the water management method. Moreover, compared with conventional natural gas and other energy resources, freshwater consumption about shale gas exploration is decreasing with the progress of exploration technology, while its life-cycle GHG emissions are greater in the long term.